Deep Learning Model in Personalizing Learning Based on the "Love Curriculum" in Islamic Boarding School - Zainab, Nurul (Proceeding International Conference on Education, 2025)
This study explores innovative deep learning-based personalized learning and the “Love Curriculum” at the Padepokan Kyai Mudrikah Kembang Kuning Islamic Boarding School in Pamekasan. The traditional educational paradigm is less adaptive to student heterogeneity, triggering the urgency for personalization. The deep learning model offers solutions for content adaptation and dynamic feedback, while the Curriculum of Love instills the values of monotheism. Through a case study, this research analyzes the implementation of these models. Data was collected from the director, teachers, and students through interviews, observations, and documentation, with data validity verified using pattern matching. The results show the systematic application of personalization, beginning with comprehensive diagnostic assessments for learning grouping and peer tutor empowerment. The learning philosophy of “joyful, conscious, meaningful” is emphasized with hands-on practices that foster spiritual empathy. All activities are based on the “unification curriculum” (monotheism). The seven pillars of Islamic Boarding School learning: one day one verse, one hadith one presentation, one week three languages, one student one laptop, one activity one paragraph, one week three fashl and one week three themes, integrate spirituality, language, literacy, and digital technology. This model develops student holistically: intellectually, spiritually, and characteristically, with the ultimate goal of monotheism.